PENGARUH MERCHANDISING, ATMOSFER TOKO, DAN PROMOSI TERHADAP IMPULSE BUYING PADA PELANGGAN TOKO PROGO PALAGAN - Afrianto, Wikri; Transistari, Ralina; Amallia, Bunga Alfausta (LP2M Universitas Bina Bangsa, 2024)
This research aims to analyze the influence of merchandising, store atmosphere, and promotions on impulse buying at the Progo Palagan Store. The development of the retail business in Indonesia continues to increase every year. The rapid development of modern retail is based on the company's desire to meet the needs of its customers. Merchandising activities and retail promotional activities can influence the occurrence of impulse buying, because unplanned purchasing behavior is unique and unpredictable consumer behavior in terms of shopping. This research used primary data and was carried out by distributing an online questionnaire using Google Form to 100 Progo Palagan Shop customers. Analysis of this research data uses multiple linear regression. This research uses model tests with goodness of fit, basic assumption tests, and classical assumption tests. The research results show that merchandising, store atmosphere, and promotions have a positive effect on impulse buying at the Progo Palagan Store. This research suggests examining the influence of personality factors and normative evaluation on impulse buying